"Walking wounded or wounded healer?" Does personal experience of mental health problems help or hinder mental health practice? A review of the literature. Issue 1 (2014) - Catherine Conchar; Julie Repper
<x xml:space="preserve"> Abstract </x> Purpose – A systematic review of the literature on "wounded healers" was undertaken to identify, define and interpret the term and its application within the mental health environment. The paper aims to discuss these issues. Design/methodology/approach – Eight key medical/social sciences databases were interrogated. In total, 835 papers were identified in the systematic database search and abstracts were obtained for each to determine whether they met the inclusion criteria. In total, 237 sources were retrieved for critical reading, to assess relevance and value to the review, and 125 documents were subsequently included. Through thematic analysis a number of themes and sub themes were identified Findings – The archetypal image of the wounded healer originates in ancient mythology and crosses many cultures. There are many interpretations and applications of the belief that having healed their own wounds a person is in a better position to heal others, however, the evidence to support this is not so robust. Of more direct relevance to contemporary practice are reports of supporting staff with mental health problems to make a contribution to mental health services, most recently through the employment of peer support workers. Originality/value – As peer support workers are increasingly being employed in mental health services, it is helpful to consider the many existing staff who bring personal experience of mental health problems. This paper explores the evidence that their lived experience makes a difference to the way that they work and considers their employment support needs.